Knowledge, attitude and practice of using antibiotics as self-medication among non-medical graduates - V, Asha; Yadav, Karthik D (International Journal of Dental Research, 2017)
Background: Antibiotic abuse is a major concern in the modern era of internet. The ease of availability of drugs, lack of time to visit a doctor, poverty, the lack of knowledge about antibiotics, the influence of relatives, friends and advertising media seems to be the major contributing factors for self-medication. The objective of the study was to assess the knowledge, attitude and practice of antibiotics as self-medication among non-medical graduates.Methodology: A validated, self-administered questionnaire on knowledge, attitude and practice was used to collect data from 400 non-medical graduates.Results: Statistical analysis was done by Chi-square and Multiple response test. Results revealed that 163(68%) B.E and 95(59%) B.Com graduates were aware of antibiotics. Majority of graduates (>90%) in both the groups have the opinion that antibiotics are â€œOver the Counterâ€ (OTC) drugs and that they have adverse effects.Conclusion: Majority of B.E and B.Com graduates were aware of antibiotics, but not of their side effects. They had the misconception that antibiotics are â€œOTCâ€ drugs. The most common reason for self-medication was the previous use of same medication.